2013
DOI: 10.1002/cem.2576
|View full text |Cite
|
Sign up to set email alerts
|

Determination of rice type by 1H NMR spectroscopy in combination with different chemometric tools

Abstract: A 400-MHz 1H nuclear magnetic resonance (NMR) spectroscopy and multivariate data analysis were used in the context of food surveillance to discriminate 46 authentic rice samples according to type. It was found that the optimal sample preparation consists of preparing aqueous rice extracts at pH 1.9. For the first time, the chemometric method independent component analysis (ICA) was applied to differentiate clusters of rice from the same type (Basmati, non-Basmati long-grain rice, and round-grain rice) and, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The range of applications of multivariate methods spreads from pharmaceutical products and foodstuff to complex environmental samples and clinical diagnostics [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The range of applications of multivariate methods spreads from pharmaceutical products and foodstuff to complex environmental samples and clinical diagnostics [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has recently been shown that an alternative approach, namely independent components analysis (ICA) can outperform standard PCA for data reduction and can even be applied for solving classification problems [25][26][27][28]. The goal of ICA is to recover the "pure" source signals from a data set of mixed signals by finding a transformation that minimizes the dependencies between "pure" source signals (called ICs) [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our experience, the "pure" source signals extracted by ICA represent chemically significant sources in comparison with "abstract" PCA loadings [25][26][27][28][29][30]. The proportions of each "pure" source signal in the mixed signal of each sample can be compared to PCA scores for the visualization of the groups of objects [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another recent study, ICA in conjunction with conventional chemometric methods, such as PCA, linear discriminant analysis (LDA), factorial discrim inant analysis (FDA), projections to latent structures discriminant analysis (PLS-DA), soft independent modeling of class analogy (SIMCA), has been used for discriminating samples of rice regarding their varieties and geographical origin on the basis of 1 H NMR spec troscopy [18]. ICA modeling enabled a complete sep aration Basmati rice from other varieties of long grain rice, which is impossible with conventional PCA.…”
mentioning
confidence: 99%